Parenthood Between Generations Transforming Reproductive Cultures - Pooley, Siân; Qureshi, Kaveri (Berghahn Books, 2016)
Recent literature has identified modern "parenting" as an expert-led practice-one which begins with pre-pregnancy decisions, entails distinct types of intimate relationships, places intense burdens on mothers and increasingly on fathers too. Exploring within diverse historical and global contexts how men and women make-and break-relations between generations when becoming parents, this volume brings together innovative qualitative research by anthropologists, historians, and sociologists. The chapters focus tightly on inter-generational transmission and demonstrate its importance for understanding how people become parents and rear children.